BIOGEOCHEMICAL LICHEN-INDICATION STUDY OF THE STATE AND DYNAMICS OF THE ATMOSPHERIC POLLUTION OF THE ARBORETUM OF THE FALZ-FEIN BIOSPHERE RESERVE "ASKANIA NOVA" - Tyutyunnik, Yu.; Shabatura О.; Blum О. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
By the method of biogeochemical lichen indication on the territory of the arboretum of the Falz-Fein Biosphere Reserve "Askania-Nova" (Kherson Region, UKRAINE) the temporal trends (2011-2021) in the concentrations of heavy metals and other micro- and macro-elements in the epiphytic lichens was estimated. The lichens samples of Parmelia sulcata, Xanthoria parietina and Evernia prunastri collected in 2011 (39 sites) and 2021 (44 sites) for the concetrations of 22 chemical elements (Al, B, Ba, Ca, Cd, Cr, Co, Cu, Fe, K, Mg, Mn, Na, Ni, Pb, S, Sb, Se, Sr, Ti, V and Zn) by the ICP-OES spectroscopy were analysed. In order to correctly compare the concetrations of elements in different species of lichens, their intercalibration to the base species P. sulcata was carried out and the calibration coefficients, the so-called biogeochemical lichen indicies (BGCHL indicies), were calculated. Based on these indicies the arithmetically averaged hypothetical concetrations of elements in lichen samples collected at the sites, where P. sulcata was absent, were calculated and corresponding databases of element concentrations for all three species were created. Factor analysis was applied to identify possible sources of the elements determined in the lichens for the period of 2011 (Fa-1 – Fa-8) – 2021 (Fb-1 – Fb-8). The eight resulting factors represent crust and anthropogenic components. Some of the factors were interpreted as being associated with the agricultural activities, microclimate, pH of atmospheric precipitation and with the higher plants factor (leaching of еlements and their absorption by lichens). The factor structure of the chemical elements concetrations in the lichens growing on the studied area was formed under regional conditions of the accumulation of Cr, Na, Ti, as well as a decrease in the concetrations of such elements as V, Zn, Mn, Cu, Mg, K, Sr, Ba, Pb, Ni, Ca, S and Se. Moreover, Sb and Ba have spatially heterogeneous dynamics of their concetrations, and Se has very heterogeneous dynamics with a decreasing trend of the concentrations.